Alternative Education Systems Implementation Guide - Ministry of Education, Science and Technology (Republic of South Sudan, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:4DIC26K5 2405685:883F3NWN

National Education Policy - Ministry of Education, Science and Technology (Government of the Republic of Malawi, 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:FY73KUN5 2405685:ZN289ZGZ

Education Sector Analysis - Ministry of Education, Science, and Technology (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Education Sector Analysis - Ministry of Education, Science, and Technology (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Education Sector Analysis - Ministry of Education, Science, and Technology (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Education Sector Development Plan (2016/17 – 2020/21). Mainland Tanzania. - Ministry of Education, Science and Technology (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:LQ7NJLCK 2405685:YLZWG8IQ

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Government of Sierra Leone; UNICEF, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:843DCCS6 2405685:HZ89SJYF

Education Sector Plan, 2018-2020: Getting It Right – Service Delivery, Integrity and Learning in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:AIISD4KD 2405685:DFHS5ZVL

Sierra Leone: Education Country Status Report: An analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2013)
KerkoCite.ItemAlsoKnownAs: 2405685:FWX5GT4H

Education sector development plan 2016/17 – 2020/21: Tanzania mainland - Ministry of Education, Science and Technology (The United Republic of Tanzania, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:876JM6DJ 2405685:IGRKA5BU

Education sector performance report 2017/2018: Tanzania mainland - Ministry of Education, Science and Technology (United Republic of Tanzania, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:G5TB2VDG 2405685:V5BDM7A3

National Framework for Continuous Professional Development for Practicing Teachers - Ministry of Education, Science and Technology (United Republic of Tanzania, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:F5D7RDCT 2405685:GFCJSMIU 2405685:SFYUBD4B
Keywords: _B:important; _G:important; _G:reviewed; _Tanzania; _final_bib; _important

Education sector development plan 2016/17–2020/21: Tanzania mainland - Ministry of Education, Science and Technology (The United Republic of Tanzania, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:P9N9FWTP 2405685:EJXB68SF

Education Sector Analysis - Ministry of Education, Science, and Technology (Government of the Republic of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Ministry of Education, Science and Technology – Policy Reforms - Malawi Ministry of Education, Science and Technology (2019)
The Malawi Public Sector Reforms Management Unit exists to catalyse, drive and facilitate public sector reforms in Malawi. The reforms are implemented in Government ministries, departments and agencies (MDAs), local councils, parastatal organizations and constitutional bodies.
KerkoCite.ItemAlsoKnownAs: 2339240:CVBB75DU 2405685:Z4Z43LCT

Kaduna State Education Sector Strategic Plan 2019–2029 - Kaduna State Ministry of Education, Science, and Technology (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:TCQAI8WV 2405685:GBMN8DMP

Education Sector Plan 2018-2020 - Ministry of Education, Science and Technology (Sierra Leone) (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:24PRFKEK

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Sierra Leone) (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:GVAZB6TM

Malawi Education Sector Analysis - Malawi Ministry of Education, Science, and Technology, Malawi (Government of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:D5NERCHI 2405685:UKTVQWTU

Global Initiative on Out-of-School Children: Tanzania Country Report - UNICEF; Ministry of Education, Science and Technology; UNESCO (UNICEF, United Republic of Tanzania, UNESCO, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:4BFXL5NI 2339240:MZX7KWXD 2405685:FZLBUYAH 2405685:IRZRMTPE